2022
DOI: 10.1002/trtr.2146
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Small‐Group Reading Instruction

Abstract: In this article, the authors revisit the common practice of small‐group reading instruction. They challenge the idea of grouping readers based on text levels and instead review supplemental intervention group research that suggests targeted skill practice as a more optimal use of time in small groups. They then present the ABCs—a focus on assessment, basics & books, and clarity in communication—as the central principles that should guide how we instruct reading in small groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…(1) Use CAPS in Small-Group Instruction. We have found that embedding CAPS into small-group instruction (see Conradi Smith et al, 2022) works well because teachers are already using assessments to consider individual needs. The designated space for doing different activities with different students also offers opportunities for student choice.…”
Section: Recommendations For Shifting To a Caps Approachmentioning
confidence: 99%
“…(1) Use CAPS in Small-Group Instruction. We have found that embedding CAPS into small-group instruction (see Conradi Smith et al, 2022) works well because teachers are already using assessments to consider individual needs. The designated space for doing different activities with different students also offers opportunities for student choice.…”
Section: Recommendations For Shifting To a Caps Approachmentioning
confidence: 99%
“…Differentiated reading groups have the following characteristics: Groups formed using literacy assessment data : Although Fountas and Pinnell's (2012) model formed groups based on reading level, a growing consensus among scholars emphasizes group formation based upon specific instructional needs such as those related to decoding, fluency, and/or comprehension (Conradi Smith et al., 2022; Walpole & McKenna, 2017). All agree that groups change based on students' changing needs identified using literacy assessment data (Conradi Smith et al., 2022; Fountas & Pinnell, 2012; Walpole & McKenna, 2017).…”
Section: Differentiated Reading Groups and Culturally Sustaining Peda...mentioning
confidence: 99%
“…Differentiated reading groups have the following characteristics: Groups formed using literacy assessment data : Although Fountas and Pinnell's (2012) model formed groups based on reading level, a growing consensus among scholars emphasizes group formation based upon specific instructional needs such as those related to decoding, fluency, and/or comprehension (Conradi Smith et al., 2022; Walpole & McKenna, 2017). All agree that groups change based on students' changing needs identified using literacy assessment data (Conradi Smith et al., 2022; Fountas & Pinnell, 2012; Walpole & McKenna, 2017). Targeted strategy instruction : Scholars have found that targeted strategy instruction (teaching a specific strategy or two), rather than teaching a range of strategies, is most effective (Hall & Burns, 2018; Walpole & McKenna, 2017).…”
Section: Differentiated Reading Groups and Culturally Sustaining Peda...mentioning
confidence: 99%
See 2 more Smart Citations